Mastery Learning of Video Laryngoscopy Using the Glidescope in the Emergency Department. Issue 5 (October 2016) - Ahn, James; Yashar, Michael D.; Novack, Jared; Davidson, Joey; Lapin, Brittany; Ocampo, Jose; Wang, Ernest
Abstract : Introduction: According to the Accreditation Council for Graduate Medical Education emergency medicine requirements established before the popularity of video laryngoscopy (VL) use, 35 intubations are necessary for graduation. Our study aimed to establish a mastery-learning model for a skill set very different (VL) from direct laryngoscopy (DL) and to determine the number of attempts needed to achieve mastery with VL. Methods: With the use of a randomized, controlled crossover study design, two learner groups underwent baseline testing intubating a mannequin using VL. Afterward, the intervention group received a mastery training intervention. After training, learners were required to repeat the procedure until achievement of 100% on the checklist for two consecutive attempts was achieved. After 3 months, both groups returned for retesting, and the control group received the same mastery training as the intervention group. Both groups returned for final testing after another 3 months. Results: The intervention arm had an improvement in performance versus the control arm at 3 months of total time ( P < 0.05). Both groups had an improvement within their groups' checklist scores at 3 months after training ( P < 0.05), and within the intervention arm, this effect was sustained at 6 months ( P < 0.05). There was no significant difference in the mean required attempts to demonstrate mastery (overall, 2.5; intervention, 2.75; control 2.25; P = 0.28). Conclusions: Simulation-based mastery-learning produces skill enhancement with VL that is resistant to decay across 6 months. Furthermore, although a small number of attempts are needed to achieve mastery, clinical experience did not substitute as a proxy for skill acquisition. This mastery-learning model provides skill sets that are not otherwise obtained in the clinical curriculum in a 3-month period. Abstract : Supplemental digital content is available in the text.